Systematic Literature Review: The Application of Brain-Based Learning Model on Mathematics Concept Understanding Ability - Husein Nasution, Sofyan; Deniyanti Sampoerno, Pinta; Aurelia Hidajat, Flavia (Edumaspul: Jurnal Pendidikan, 2025)
The purpose of this study is to explain and convey information about the connection between the Brain Based Learning model and students' conceptual understanding abilities in classroom learning. The method that will be applied in this study is a literature study, one of which is based on the Systematic Literature Review (SLR), which aims to discuss in depth the discussion and formulation of problems from several previous literatures that are relevant to the topic discussed. The technique used in this study uses the PRISMA protocol basis. Some of the characteristics of the literature sources used or discussed are indexed by Sinta and Scopus, available on the Google Scholar platform; Researchgate; and Eric Journal with the year of publication of the source in the last 10 years. The topics and discussions discussed in this study are related to the application of the Brain Based Learning model to students' mathematical conceptual understanding abilities and the success of the application of the Brain Based Learning model in developing students' mathematical conceptual understanding abilities. From the results of the analysis, it was found that several stages of BBL themselves were able to direct students to be able to train their mathematical conceptual understanding abilities during learning. BBL can change students' learning activities to be better in developing their mathematical conceptual understanding abilities.